2002
DOI: 10.1002/gcc.10068
|View full text |Cite
|
Sign up to set email alerts
|

The microcell hybrid‐based “elimination test” identifies a 1‐Mb putative tumor‐suppressor region at 3p22.2–p22.1 centromeric to the homozygous deletion region detected in lung cancer

Abstract: We have previously shown that inoculation of human chromosome 3 (chr3)/A9 mouse fibrosarcoma microcell hybrids (MCHs) into severely combined immunodeficient (SCID) mice was followed by the regular elimination of certain 3p regions, whereas a 3q region was retained even after prolonged mouse passage. Using this approach, referred to as the elimination test (Et), we identified a common eliminated region (CER) of about 7 cM at 3p22-p21.3 that was absent in all tumors generated from five MCHs. A second frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This gene was disrupted by CER1 centromeric border in the SCID tumours of the first Et experiments. 13,48 Northern blot analysis produced a strong signal in heart and skeletal muscle and a weak signal in kidney. In our present RT-PCR analysis, the LRRC2 transcript was detected in normal human kidney, but not in any of the 5 RCC cell lines analyzed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This gene was disrupted by CER1 centromeric border in the SCID tumours of the first Et experiments. 13,48 Northern blot analysis produced a strong signal in heart and skeletal muscle and a weak signal in kidney. In our present RT-PCR analysis, the LRRC2 transcript was detected in normal human kidney, but not in any of the 5 RCC cell lines analyzed.…”
Section: Discussionmentioning
confidence: 98%
“…1). 7,[11][12][13] In the following experiments, additional to the 5 MCHs studied in the first round of Et, we introduced 3 A9-based monochromosomal MCHs that carried cytogenetically intact human chr3 from 3 different normal donors. From these MCHs, we obtained 9 SCID mouse tumours (3 from each hybrid) that, in contrast with 5 MCHs previously studied, 11,12 remained positive for all of the 120 3p-specific PCR-markers tested (''chr31'' tumours).…”
mentioning
confidence: 99%
“…CER2 was missing from all 30 analyzed tumors derived from five microcell hybrids (MCHs). Seven genes, Golgi peripheral membrane protein coding gene p65 (FLJ23443 or Q9BQQ3), AXIN1 up-regulated (AXUD1), chemokine (C-X3-C) receptor 1 (CX3CR1), chemokine (C-C motif) receptor 8 (CCR8), hypothetical protein FLJ20551 (FLJ20551) coding gene, laminin receptor 1 (LAMR1), and myelin-associated oligodendrocyte basic protein coding gene (MOBP), have been identified within CER2 (Kholodnyuk et al, 2002).…”
Section: Elimination Testmentioning
confidence: 99%
“…Two more regions identified in our system (16,17) and four well characterized deletion hot-spot regions found in tumor biopsies and cell lines (6,7,18,19) are located at 3p12-22 (see Table 1, which is published as supporting information on the PNAS web site, www.pnas.org). Comparing human and mouse genomic sequences assembled by the Celera Discovery System, we found that CBRs localize preferentially within the tumorassociated deletions in this chromosomal segment.…”
mentioning
confidence: 97%